A comparison of the milk production potential of kikuyu (Pennisetum clandestinum) and 'Mott' dwarf elephantgrass (Pennisetum purpureum) - Brand, Coenraad Johannes Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric.) -- Stellenbosch University, 1998.